Antecedent Of Organizational Commitment In A Small-Medium Industry Context - Lila Bismala; Yayuk Hayulina Manurung (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to analyze the role of job satisfaction in moderating the relationship between organizational culture, transformational leadership, and organizational commitment, as it is known that the unit of analysis is workers in small and medium industries. This provides benefits in managing human resources, industrial relations and organizational behavior in the context of SMEs, so that optimal human resource management results in optimal competitiveness as well. The results found that job satisfaction can be an intervening variable for organizational learning and transformational leadership on organizational commitment. The results found that organizational culture affects job satisfaction and organizational commitment, and transformational leadership affects organizational commitment. But, leadership was found do not have influence on job satisfaction and job satisfaction did not have an influence on organizational commitment. On the other hand, job satisfaction was found as an intervening variable for organizational culture and transformational leadership in influencing organizational commitment. This research contributes to enriching the theory of organizational behavior in the context of SMEs.